Presence of liver metastasis correlated with high tumor abundance and indicated adverse prognostic feature in EGFR mutation non-small-cell lung cancer patients - Piyada Sitthideatphaiboon; Pronwasun Simseekeaw; Chinachote Teerapakpinyo; Nicha Zungsontiporn; Wariya Chintanapakdee; Itthi Itthisawatpan; Shanop Shuangshoti; Virote Sriuranpong; Thanisa Tongbai; Chanida Vinayanuwattikun (Scientific Reports)
Abstract EGFR-TKIs are effective therapies for non–small cell lung cancer (NSCLC) patients with EGFR-activating mutations. However, responses vary within individuals and resistant disease inevitably emerges. A prospective cohort of 130 patients with advanced EGFR mutation NSCLC were enrolled. Pre-and post-treatment plasma from subjects treated with EGFR-TKIs were obtained. The correlation between EGFR mutation abundance using the Idylla™ ctEGFR mutation assay, radiographic assessment, and clinical outcomes were analyzed. Eighty-nine patients with retrieved blood collection were analyzed. Undetectable ctEGFR (49.5%), detectable ctEGFR CqMut-high (23.5%), and detectable ctEGFR CqMut low (27%) using CqMut cutoff at 28.1, represented consecutive incremental tumor burden by radiographic assessment and outcome of treatment. Median PFS was 13.4 months [95% CI 12.0-14.8] in undetectable ctEGFR, 10.4 months [95% CI 9.9–10.9] in ctEGFR CqMut-high, and 5.9 months [95% CI 3.8–7.4] in ctEGFR CqMut-low. Number of metastasis sites > 3 was found in 22.7%, 23.8%, and 58.3% of the 3-tier ctEGFR tumor burden levels, respectively (p-value 0.01). Presence of liver metastasis was significantly correlated with number of metastasis sites > 3 and ctEGFR CqMut-low (45.8%). Liver metastasis was an independent factor of reduced PFS and OS by multivariate analysis with an HR = 2.41 [95% CI 1.27–4.60, p-value 0.007]) and HR = 2.96 [95% CI 1.35–6.51, p-value 0.007], respectively. The pretreatment ctEGFR detection using the Idylla™ ctEGFR mutation assay served as a surrogate marker for tumor abundance and tumor burden. Presence of liver metastasis was found to be a clinical predictor associated with high tumor abundance and worsening treatment outcomes.